New prospects on cerebellar reserve: Remarks on neuroprotective effects of experience in animals and humans - Gelfo, Francesca; Serra, Laura; Petrosini, Laura (Frontiers in Systems Neuroscience, 2023)
The ability of the brain to change structure and function in response to experience accounts for its ability to successfully adapt to the environment in both learning processes and unique phases, such as during development and repair. On this basis, the occurrence of brain, cognitive, and neural reserves has been advanced to explain the discrepancies between the extent of neurological damage and the severity of clinical manifestations described in patients with different lifespan experiences. Research on this topic highlighted the neuroprotective role of complex stimulations, allowing the brain to better cope with damage. This framework was initially developed by observing Alzheimer’s disease patients, and it has since been progressively expanded to multifarious pathological states. The cerebellum is known to be particularly responsive to experience through extensive plastic rearrangements. The neuroprotective value exerted by reserve mechanisms appears to be suitable for basic neuronal plasticity in the cerebellum. Thus, it is of primary interest to deepen our understanding of how life experiences modify individuals’ cerebellar morphology and functionality. The present paper is aimed at analyzing the evidence provided on this topic by animal and human studies. For animals, we considered the studies in which subjects were submitted to enhanced stimulations before the damage occurred. For humans, we considered studies in which previous lifelong high-level experiences were associated with superior cerebellar abilities to cope with injury. Detailed indications of the processes underlying cerebellar reserves may be important in proposing effective interventions for patients suffering from pathologies that directly or indirectly damage cerebellar functionality.